ACTING SKILLS IN WORKING WITH IMAGINARY OBJECTS AND ITS PSYCHOLOGICAL BASIS - Zamira Akhmedova (Modern American Journals, 2026)
This article analyzes one of the most essential elements of acting—the process of working with imaginary (non-existent) objects. Based on K.S. Stanislavski’s principle of the "magic if" and Michael Chekhov’s theory of inner psychological energy, the study explores methods for achieving harmony between an actor’s attention, imagination, and physical action.
Keywords: Magic if, scenic attention, creative imagination, inner energy, space, physical action, psychological justification.